GAMBARAN KESIAPAN IBU DENGAN DUAL-CAREER MENJALANI MASA TRANSISI ANAK MENUJU SEKOLAH DASAR - Dewi Rayani (Journal of Mandalika Literature, 2021)
The transition period from childhood to elementary school is categorized as a transition period. This period requires special attention from various parties, both teachers, parents and schools. Parents have a major role, because with the readiness of parents to accompany children, children are easy to adapt and socialize in new environments. The respondents in this study were 3 mothers with dual carriers. Data analysis using interpretive phenomenological analysis. The results of the study show that there are two types of readiness, namely physical and psychological readiness. Physical readiness is described by a healthy physique, not stress two. While psychological is described by the ability of parents to manage emotions, be good listeners, always apply positive parenting patterns and use effective communication.